SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN DESAIN INTERIOR MENGGUNAKAN LOGIKA FUZZY SUGENO - jarti, nanda (Jurnal EDik Informatika, 2020)
Batam City is a city that is growing rapidly, in terms of development, it is getting more and more, Everyone is competing to make an attractive Interior Design so that many visitors. Interior design can be seen in terms of aspects such as price, interior design and shape. The purpose of this study is to help users choose interior designs according to their needs. This Design Selection Case uses Fuzzy Logic by using Sugeno method to determine the input and output variables which are company associations, then converting the input variables into fuzzy sets with the fuzzification process, then fuzzy processing controls the data with the minimum method. The final step is to convert the output into a set of deficits with a defuzzification process using the centroid method, so that the desired results will be obtained in the output variable. This study uses education, age, opportunity and company variables using mathematical constants or input variable functions, and in the defuzzification process using the centralized mean method. The result of this research is that using the Sugeno method in fuzzy logic can be a Decision Making System in the selection of Interior Design in Batam City.